Adaptive sliding-mode trajectory tracking control for state constraint master–slave manipulator systems. (August 2022) - Cruz-Ortiz, David; Chairez, Isaac; Poznyak, Alexander
Abstract: This study aims to propose an adaptive state-dependent gain finite-time convergent controller (using the fundamentals of the sliding mode theory) that solves the trajectory tracking for a class of state constraint master–slave robotic system (M-SRS) formed by two manipulators with the same number of articulations. The control design considers the effect of state constraints by implementing a state dependent adaptive gain. A Lyapunov-stability analysis leads to design the gain variation laws yielding proving the finite-time convergence of the sliding surface as well as the asymptotic convergence of the tracking error. The state constraints of the slave system motivate the characterization of the convergence-time as a function of the bounded uncertainties affecting the M-SRS dynamics. The forward-complete setting of the M-SRS justified the application of a robust and exact differentiator which estimated the articulation velocities for the slave robot. The estimated velocities are used as part of the realization of the output feedback controller. Numerical simulations demonstrate that the proposed control scheme provides a smaller quadratic norm of the tracking error compared with the obtained with other controllers (proportional–derivative and conventional sliding modes). The proposed control approach satisfies the state constraints while the sliding manifold converges to the origin in finite-time as justified by the theoretical stability analysis. Highlights: An adaptive gain finite-time controller solves the trajectory tracking of state-constraint robot. The control design considers constraints by implementing an adaptive gain. A Lyapunov-stability analysis serves to design the gain variation law. The state constraints for the slave system motivate the definition of the convergence-time. Numerical simulation served to confirm the theoretical findings.